Ultrasonographic Evaluation of Morphological Changes in Peripheral Nerves after Traumatic Injury and Nerve Repair – A Prospective Study - Dietrich, Léna G.; Juon, Bettina; Wirtz, Christian; Vögelin, Esther (Ultrasound International Open, 2024)
Purpose Ultrasound (US) has gained in importance for the visualization of morphological changes of injured nerves. After surgical repair, changes in neural structures are seen over time. The correlation of morphologic changes in US with the corresponding nerve function is uncertain. The aim of this study is to determine a correlation of post-traumatic morphological nerve changes with US and with nerve function after surgery.Materials and Methods This dual-center, prospective cohort study was conducted between 2017 and 2022 and included 20 mixed sensory motor nerve lesions. Patients were followed up clinically (sensitivity, pain, and motor function) with US and electroneuromyography. We determined the US changes of the nerves including the interaction of the tissue after nerve repair and any correlation with nerve function. With US nerve cross-sectional area (CSA), the number of traversing fascicles, hypo-echogenicity, and presence of perineural scar were analyzed.Results 20 lesions (12 median and 8 ulnar nerves) of 18 patients with intraoperatively confirmed nerve injury of at least 50% in the forearm were included. The average CSA was over 20 mm2 throughout the follow-up period, corresponding to a neuroma in continuity compared to the opposite side (10.75 mm2). Sensibility and motor function at 12 months were 6xS3/4 and 10xM3-5. There was a statistically significant correlation between continuous fascicles on US at 6 months and sensitivity at 12 months. Conclusion This study supports the presence of post-traumatic morphological changes in nerve fibers with US after traumatic injury. Morphological changes in nerve structure after trauma can be detected with US indicating a correlation between continuity of nerve fascicles and development of sensitivity and motor function.
Keywords: ultrasound; morphologic changes; upper extremities